PENANAMAN NILAI-NILAI PENDIDIKAN KARAKTER MELALUI SISTEM PEMBELAJARAN PESANTREN DI SMP NEGERI 2 ASEMBAGUS SITUBONDO TAHUN PELAJARAN 2016/2017 - Minhaji Minhaji; Kiki Hermawanti (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2017)
This thesis discusses about the Cultivation of Values ​​of Character Education through Pesantren Learning System in SMPN 2 Asembagus. The main questions that will be answered through this research are: (1) The Cultivation of Values ​​of Character Education in SMPN 2 Asembagus ?, (2) The Role of Pesantren Learning System in Cultivating the Values ​​of Character Education in SMPN 2 Asembagus ?. To answer the question then discussed through field study conducted in SMP Negeri 2 Asembagus with descriptive qualitative approach. The findings of this study indicate that the values ​​of character education are very important to be inculcated through the learning process in school. Education is required to be able to change the students towards the better. The values ​​in character education are expected to be able to print the next generation of strong character through the pesantren learning system. Pesantren learning system in question is through pengajian taysirul kholaq book. The results showed: (a) the values ​​of character education that have been implanted in SMP Negeri 2 Asembagus is Faith / Religion, Honesty, Self, Discipline, Friendly / Communicative, Curiosity, Hard work, Democracy, Love of Peace, Care for the environment and Maintain cleanliness, Social Care, Spirit of nationality and Love of the homeland. (b) the role of the pesantren learning system in inculcating the values ​​of character education is closely related to have the same orientation of character formation. The value of the characters embedded in the students in SMP Negeri 2 Asembagus is obtained through the study of Taysirul Kholaq as the teaching stage of moral values ​​(Moral Knowing) and the habituation done by the students (Moral Action) so as to give birth to the students with positive character (Moral Feeling).